1993
DOI: 10.1136/bmj.306.6894.1728
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical guidelines improve general practice management and referral of infertile couples?

Abstract: Objective-To evaluate guidelines for general practice management and referral of infertile couples. Guidelines were implemented with a disease specific reminder at the time of consultation (the guidelines were embedded within a structured infertility management sheet for each couple).Design-Pragmatic randomised controlled trial. Participating practices were randomised to a group that received the guidelines and a control group.Setting-82 general practices in Grampian region. Subjects-100 couples referred by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 12 publications
1
40
0
2
Order By: Relevance
“…26 Other randomised clinical trials have shown that implementation of guidelines in medical primary care are variably effective. [27][28][29][30] Furthermore, recent systematic reviews suggest that the effects of audit and feedback in improving professional practice are generally variable. 31,32 These guidelines were developed to address the shortcomings in referral practices identified in the first audit cycle.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other randomised clinical trials have shown that implementation of guidelines in medical primary care are variably effective. [27][28][29][30] Furthermore, recent systematic reviews suggest that the effects of audit and feedback in improving professional practice are generally variable. 31,32 These guidelines were developed to address the shortcomings in referral practices identified in the first audit cycle.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, we strongly disagree with diverting 2 years of an infertility patient's time into a scheme where per-cycle pregnancy rates are unknown and where most patients, even when ideally selected, will quit treatment.…”
Section: Re: Outcomes From Treatment Of Infertility With Natural Procmentioning
confidence: 99%
“…We chose to follow the recommendations of the Cochrane Collaboration, that outcomes be reported as a pregnancy rates per woman or couple, because repeat cycle data are not statistically independent and are less relevant to the patient. 6,7 More accurate comparisons of outcomes could be made if IVF clinics followed these recommendations.…”
Section: Response: Re: Outcomes From Treatment Of Infertility With Namentioning
confidence: 99%
“…Requiring all EMS providers in North Carolina to follow the protocols, procedures, policies, and other relevant sections in the NCCEP document ensures a minimum baseline level of care and helps standardize prehospital care throughout the state. It has been shown that standardizing patient care reduces variation in clinical practice [2][3][4]. This is particularly important in North Carolina because many providers work in multiple EMS agencies throughout the state [5].…”
Section: Standardization Of Carementioning
confidence: 99%